A study of sociocultural factors in the decline of the birth rate based on a survey of women - Li Jiafeng, Zhao (Journal of the Belarusian State University. Philosophy and Psychology, 2026)
This article examines the sociocultural factors behind China’s declining birth rate. It analyses the economic, social, cultural, psychological, and biological causes of the demographic crisis, as well as the impact of urbanisation, career ambitions, and changing values on women’s reproductive behaviour. It presents the results of a survey of 400 Chinese women. Particular attention is paid to the consequences of China’s one-child policy and traditional gender roles. Measures to support families and increase the birth rate are proposed.
Keywords: birth rate; women; career; motherhood; urbanisation; traditions; values; social policy; demography; gender roles